1996
DOI: 10.1074/jbc.271.32.19025
|View full text |Cite
|
Sign up to set email alerts
|

The Mixed Lineage Kinase SPRK Phosphorylates and Activates the Stress-activated Protein Kinase Activator, SEK-1

Abstract: SPRK (also called PTK-1 and MLK-3), a member of the mixed lineage kinase subfamily of (Ser/Thr) protein kinases, encodes an amino-terminal SH 3 domain followed by a kinase catalytic domain, two leucine zippers interrupted by a short spacer, a Rac/Cdc42 binding domain, and a long carboxyl-terminal proline-rich region. We report herein that SPRK activates the stress-activated protein kinases (SAPKs) but not ERK-1 during transient expression in COS cells; the p38 kinase is activated modestly (1.3-2 fold) but cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
206
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(215 citation statements)
references
References 28 publications
6
206
1
2
Order By: Relevance
“…Recently, mouse PAK3, another STE20 family member, has been shown to bind the SH3 domains of phospholipase Cg and Nck in vitro . Finally, the mixed lineage kinases, SPRK contains SH3 domains and functions as an activator of the JNK/SEK pathway (Rana et al, 1996). Examination of KHS's ability to bind various SH3-containing proteins is under way.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mouse PAK3, another STE20 family member, has been shown to bind the SH3 domains of phospholipase Cg and Nck in vitro . Finally, the mixed lineage kinases, SPRK contains SH3 domains and functions as an activator of the JNK/SEK pathway (Rana et al, 1996). Examination of KHS's ability to bind various SH3-containing proteins is under way.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, The small GTPases such as Rac and CDC 42 fail to activate MKK3 (Han et al, 1996). However, the recently identi®ed MKKKs such as apoptosis signal regulating kinase or ASK1 (Ichijo et al, 1997), MEKK4/MTK1 (Takekawa et al, 1997), TGFbactivated kinase-1 or TAK1 (Shirakabe et al, 1997) and mixed lineage kinase-3 or MLK3 (Rana et al, 1996;Tibbles et al, 1996) appear to activate MKK3. The identity of the upstream small GTPases and kinase(s) involved in the activation of MKK3 is yet to be de®ned.…”
Section: Map Kinase Kinase-3mentioning
confidence: 99%
“…In contrast to MAPKs and MAPKKs, the MAPKKKs in the JNK and p38 modules are highly divergent in structure and gene number. To date, eleven di erent MAPKKKs have been identi®ed as upstream activators of JNK pathway (Widmann et al, 1999); MEKK1 (Lange et al, 1993), MEKK2 (Blank et al, 1996), MEKK3 (Blank et al, 1996), MTK1/ MEKK4 (Takekawa et al, 1997;Gerwins et al, 1997), Tpl-2/Cot (Aoki et al, 1991;Salmeron et al, 1996), MUK/DLK/ZPK Holzman et al, 1994;Reddy and Pleasure, 1994), MLK-2/MST (Dorow et al, 1995;Hirai et al, 1997), MLK-3/SPRK/ PTK-1 (Rana et al, 1996;Gallo et al, 1994;Ing et al, 1994), TAK1 (Yamaguchi et al, 1995), ASK1/ MAPKKK5 Ichijo et al, 1997) and ASK2 (Saitoh and Ichijo, unpublished observation)/MAPKKK6 (Wang et al, 1998) have been shown to activate JNKs by overexpression (Figure 1). Of these, MEKK1, MEKK2, MEKK3 and Tpl-2 can also activate the ERK pathway, while only TAK1, ASK1 and MTK1 have been shown to strongly activate p38s as well.…”
Section: Upstream Kinases In the Jnk And P38 Modulesmentioning
confidence: 99%